1998
DOI: 10.1021/jp9814449
|View full text |Cite
|
Sign up to set email alerts
|

Flash Photolysis of 1,3-Dichloro-1,3-diphenylpropane in Polar Solvents:  Generation of a Stabilized γ-Chloropropyl Cation, Subsequent Formation of a Propenyl Cation, and Nucleophilic Trapping of Both Cations

Abstract: Photolysis of 1,3-dichloro-1,3-diphenylpropane (1) in 2,2,2-trifluoroethanol at 266 nm leads to a γ-chloropropyl cation (2a) following loss of chloride ion. Kinetic evidence has been obtained for the interconversion between the open chain cation and the corresponding cyclic chloronium ion (2b); thermal loss of hydrogen chloride gives the 1,3-diphenyl-2-propenyl cation (3). The formation of this species occurs through a monophotonic process; the involvement of a two-photon process in the photoheterolysis of dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…4a, red line). Two new absorption bands at 360 and 490 nm are clearly observed, which correspond to intermediates I and II , respectively, based on literature data 45 . The lifetime of the carbocation INT II also depends on the nucleophilicity of the anionic leaving group (see Supplementary Information Fig.…”
Section: Resultssupporting
confidence: 55%
“…4a, red line). Two new absorption bands at 360 and 490 nm are clearly observed, which correspond to intermediates I and II , respectively, based on literature data 45 . The lifetime of the carbocation INT II also depends on the nucleophilicity of the anionic leaving group (see Supplementary Information Fig.…”
Section: Resultssupporting
confidence: 55%
“…Photolysis of 1,3-dichloro-1,3-diphenylpropane in 2,2,2-trifluoroethanol (TFE) at 266 nm leads to the γ-chloroalkyl cation. Similarly to other γ-chloroalkyl cations, this species thermally loses hydrogen chloride, leading to the ( E,E )-1,3-diphenylpropenyl cation with characteristic absorption at λ max 490 nm (Figure ) . The possibility of two-photon generation of the latter from the dichloride has been ruled out by studying its formation at different laser intensities.…”
Section: Photochemistry Of 1n-dihaloalkanes (N > 2):  Bichromophores ...mentioning
confidence: 99%
“…Finally, the ( E,E )-1,3-diphenylpropenyl cation photoisomerizes to its ( Z,E ) stereoisomer either in rigid media or in solution . In TFE, ( Z,E )-1,3-diphenylpropenyl cation undergoes thermal reversion with a lifetime of 3.5 μs at room temperature.…”
Section: Photochemistry Of 1n-dihaloalkanes (N > 2):  Bichromophores ...mentioning
confidence: 99%
“…As the simplest multilaser chemistry, two-laser chemistry of short-lived species such as excited molecules and reactive intermediates in liquid phase has been extensively investigated by various groups. For example, Miranda et al have reported that heterolytic cleavage of C−Cl bond proceeds to give α-chloroalkylbenzyl cation and chloride ion during the first 266-nm laser flash photolysis of dichlorodiphenylalkanes, , followed by dehydrochlorination of the cation to give α- E -allylbenzyl cation, and that the α- E -allylbenzyl cation isomerizes to the Z -isomer with the second laser excitation at 480 or 532 nm. Ouchi et al have reported that two-step homolytic cleavages of two C−Br or C−Cl bonds proceed to give a biradical during two-color two-laser photolyses of 1,8-bis(bromomethyl)- and 1,8-bis(chloromethyl)naphthalenes using the first 193-, 248-, or 308-nm and second 351-nm excimer lasers .…”
Section: Introductionmentioning
confidence: 99%